2015
DOI: 10.1107/s1600577515016148
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectroscopy for chemistry in the 2-4 keV energy regime at the XMaS beamline: ionic liquids, Rh and Pd catalysts in gas and liquid environments, and Cl contamination in γ-Al2O3

Abstract: Synopsis:The performance of the XMaS beamline for soft X-ray spectroscopy in the 2-4 keV range is assessed with particular relation to in situ studies of functional materials and their chemistry. X-ray spectroscopy for chemistry in the 2-4 keV energy regime at the XMaS beamline: ionic liquids, Rh and Pd catalysts in gas and liquid environments, and Cl contamination in c-Al 2 O 3 How to cite your article in pressYour article has not yet been assigned page numbers, but may be cited using the doi:Thompson, P.B.J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 62 publications
3
26
0
Order By: Relevance
“…This allowed us to address these systems from the perspectives of the Cl K and Pd L 3 -edges using a recently developed reactor [21] that permits the study of solids in liquid flows at X-ray energies in the 2-4 keV region whilst retaining the overall approach employed in the reactor studies made at the Pd K-edge (24.35 keV). Figure 2 shows the Cl K-edge XANES obtained from each sample in their as-received state and, for the two ENCAT™ 30 NP samples (batch II and batch III), after This exercise in quantification of the degree to which the Pd in any of these Cl containing ENCAT™ samples exists in the reduced state likely overestimates the levels of Pd 0 , given the sensitivity of the Pd 0 XANES to particle size ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed us to address these systems from the perspectives of the Cl K and Pd L 3 -edges using a recently developed reactor [21] that permits the study of solids in liquid flows at X-ray energies in the 2-4 keV region whilst retaining the overall approach employed in the reactor studies made at the Pd K-edge (24.35 keV). Figure 2 shows the Cl K-edge XANES obtained from each sample in their as-received state and, for the two ENCAT™ 30 NP samples (batch II and batch III), after This exercise in quantification of the degree to which the Pd in any of these Cl containing ENCAT™ samples exists in the reduced state likely overestimates the levels of Pd 0 , given the sensitivity of the Pd 0 XANES to particle size ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The latter was configured in standard fluorescence yield geometry in the horizontal plane at 9° to the incoming X-ray beam and at 45° to the sample that was held inside a purpose built chamber described in [21].…”
Section: K and Pd L3-edge Measurementsmentioning
confidence: 99%
“…An equally plausible explanation is the displacement of some of the Cl from the Pd to Al sites on the support. At this juncture, we may surmise that the first consequence of the wetting of all the samples with ethanol-water is to remove a proportion of the Cl directly methods we have recently developed at the XMaS beamline at the ESRF [30]. Figure 3 shows the results for the dry samples, which clearly indicated the amounts of Cl retained in these catalysts -relative to the Pd loading -is considerably higher in the 1 wt-% case compared to the 5 and 10 wt-% cases.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, the data was compared to an equivalent, Pd nitrate-derived system (bottom trace), measured in the absence of solvent to confirm that the Al 2 O 3 used is, in fact, chlorine free, having previously found that certain other aluminas [30] contain considerable levels of chlorine that can interact with metals deposited. Beyond this, we may see that after having been wetted at room temperature, the residual chlorine that remains in the sample is not subsequently removed, or change significantly, through subsequent heating under the solvent flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation